THE COMPARATIVE STUDY OF SOME BODILY VARIABLES IN ARISTICHTHYS NOBILIS AND HYPOPHTHALMICHTHYS MOLITRIX - GABRIELA VASILE; ELENA CIORNEA; ELENA RADA MISĂILĂ; C. MISĂILĂ (Scientific Papers Animal Science and Biotechnologies, 2023)
The paper performs a comparative analysis of some bodily variables (maximum bodily height, circumference and bodily weight) in two cultured cyprinids species grown in a controlled system, namely: Aristichthys nobilis (bighead carp) and Hypophthalmichthys molitrix (silver carp), of various ages (starting with the first up to the fourth growth summer). The results obtained evidenced that, in the foursummer old the representatives of Aristichthys nobilis show slightly higher values than those of Hypophthalmichthys genus, for the all bodily variables taken into study.